The Role of Zakat Digitization in Mediating the Influence of Productive Zakat on Mustahik Economic Empowerment (Study on Baznas Pekalongan City) - Niddhiyah Jannah; Nur Kholidah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine and analyze the effect of productive zakat on the economic empowerment of mustahik, with zakat digitalization as a mediating variable, at the Nasional Zakat Agency (BAZNAS) of Pekalongan City. The Independent variable in this study is productive zakat, the dependent variable is the economic empowerment of mustahik, While the mediating variable is zakat digitalization. The research approach applied is Quantitative, with a sampling technique based on the Slovin formula, Which yielded 94 respondents from the population of mustahik recipients of productive zakat. The type of data used is Primary Data, collected through the distribution of questionnaires. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) via the WarpPLS 7.0 Application. The results indicate that prodictive zakat has a positive and significant effect on the economic emprowerment of zakat recipients as well as zakat digitalization. Furthermore, zakat digitalization also demonstrated a positive and significant influence on the economic emprowerment of zakat recipients. Additionally, zakat digitalization was found to mediate the economic emprowerment of zakat recipients.